The Influence of Workload and Work Stress on the Productivity of PT Aseanindo Network Solution - Nazarudin, Muhammad; Pujiati, Herni (Dinasti International Journal of Digital Business Management, 2025)
Resource management has an active role in employee productivity through several variables that influence it, such as work stress and workload. This research is quantitative wih descriptive method. Thicantfis study uses primary data obtained from the distribution of research qusstionnaires. The analysis technique uses multiplelinear regression using the SPSS application to test the partial regression coefficient with a significant level of 5%. In addition instrument testing classical assumption test, heteroscedasticity test, and hypothesis testing were also carried out. The results of this study are as follows, work stress has a significant positive effect on work productivity. Workload simultaneously has a significant positive effect on work productivity. The conclusion of this study is that there is a significant positive effect between work stress and workload on employee work productivity at PT Aseanindo Network Solutions. Suggestions for further researchers to continue further research to discuss broader topics such as adding other variables.